Persistently Altered Brain Mitochondrial Bioenergetics After Apparently Successful Resuscitation From Cardiac Arrest. Issue 9 (September 2015) - Kilbaugh, Todd J.; Sutton, Robert M.; Karlsson, Michael; Hansson, Magnus J.; Naim, Maryam Y.; Morgan, Ryan W.; Bratinov, George; Lampe, Joshua W.; Nadkarni, Vinay M.; Becker, Lance B.; Margulies, Susan S.; Berg, Robert A.
Abstract : Background: Although advances in cardiopulmonary resuscitation have improved survival from cardiac arrest (CA), neurologic injury persists and impaired mitochondrial bioenergetics may be critical for targeted neuroresuscitation. The authors sought to determine if excellent cardiopulmonary resuscitation and postresuscitation care and good traditional survival rates result in persistently disordered cerebral mitochondrial bioenergetics in a porcine pediatric model of asphyxia‐associated ventricular fibrillation CA. Methods and Results: After 7 minutes of asphyxia, followed by ventricular fibrillation, 5 female 1‐month‐old swine (4 sham) received blood pressure–targeted care: titration of compression depth to systolic blood pressure of 90 mm Hg and vasopressor administration to a coronary perfusion pressure >20 mm Hg. All animals received protocol‐based vasopressor support after return of spontaneous circulation for 4 hours before they were killed. The primary outcome was integrated mitochondrial electron transport system (ETS) function. CA animals displayed significantly decreased maximal, coupled oxidative phosphorylating respiration (OXPHOSCI + CII ) in cortex ( P <0.02) and hippocampus ( P <0.02), as well as decreased phosphorylation and coupling efficiency (cortex, P <0.05; hippocampus, P <0.05). Complex I– and complex II–driven respiration were both significantly decreased after CA (cortex: OXPHOSCI P <0.01, ETSCII P <0.05; hippocampus: OXPHOSCI P <0.03, ETSCII P <0.01). In the hippocampus, there was a significant decrease in maximal uncoupled, nonphosphorylating respiration (ETSCI + CII ), as well as a 30% reduction in citrate synthase activity ( P <0.04). Conclusions: Mitochondria in both the cortex and hippocampus displayed significant alterations in respiratory function after CA despite excellent cardiopulmonary resuscitation and postresuscitation care in asphyxia‐associated ventricular fibrillation CA. Analysis of integrated ETS function identifies mitochondrial bioenergetic failure as a target for goal‐directed neuroresuscitation after CA. IACUC Protocol: IAC 13‐001023.